Atividades antimicrobiana, citotóxica e genotóxica do óleo essencial de ocimum basilicum (lamiaceae) e do linalol - Silva, Viviane Araújo da (2015)
Staphylococcus aureus and Pseudomonas aeruginosa microorganisms are of great clinical importance because they are among the bacterial species with greater power to cause infections and which have great resistance to antibiotics. Knowing that multiple drug resistant bacteria pose a challenge for the treatment of infections, it is necessary to find new substances that are effective to combat these microorganisms. Ocimum basilicum L. (Lamiaceae) is popularly known as basil and is part of a group of medicinal plants, aromatic and culinary of great economic value. This study aimed to evaluate the chemical composition of O. basilicum and determine the antibacterial activity, cytotoxic and genotoxic of essential oil and its major compound. Its chemical composition was determined by gas chromatography and the antibacterial activity of the compounds was evaluated by determining the minimum inhibitory concentration and bactericidal inhibitory concentration by microdiluition technique, the kinetics of microbial death and those compounds association study with antibiotics standards were also analyzed. For the study of cytotoxicity was performed hemolysis test on human erythrocytes and genotoxicity the micronucleus test in rodents. Among phytochemicals, the monoterpene linalool (55.2 %) is presented as the main found. The antibacterial activity of experiments showed that the essential oil of O. basilicum and linalool showed antibacterial activity against S. aureus strains ranging from 1024 to512 μg/mL and 1024 to 32 μg/mL, respectively. As for P. aeruginosa strains the minimal inhibitory concentration of the oil was 1024 μg/mL, and some resistant strains, and linalool ranged from 32 to 1024 μg/mL. The antibacterial activity was characterized as a bactericide to the strains of S. aureus in the concentration of the compounds of MICx4 and after 8 hours of contact. The compounds of association study showed patterns with antibiotics for S. aureus strains the association of essential oil or linalool with imipenem showed a synergistic effect. As for ciprofloxacin, oil association showed antagonistic effect and linalool additive effect. Regarding the strains of P. aeruginosa oil pool or linalool with imipenem showed synergistic effect and with ciprofloxacin the relationship was indifferent. The essential oil O. basilicum and linalool showed low cytotoxicity. These data were confirmed by analyzing the cytotoxicity against erythrocytes, which showed hemolysis values below 10 % for blood type test. The analysis of the genotoxic potential of compounds revealed that they were not capable of causing DNA damage in the cells of peripheral blood from treated animals. In conclusion, these results suggest that the essential oil O. basilicum and linalool present antimicrobial effect, whether alone or in combination with antibiotics patterns, and that these compounds have low cytotoxicity and genotoxicity.